Ribociclib with letrozole vs letrozole alone in elderly patients with hormone receptor-positive, HER2-negative breast cancer in the randomized MONALEESA-2 trial - Sonke, Gabe S. (Breast Cancer Res Treat, 2017)
PURPOSE: Determine the efficacy and safety of first-line ribociclib plus letrozole in elderly patients with HR+, HER2− advanced breast cancer. METHODS: 668 postmenopausal women with HR+, HER2− advanced breast cancer and no prior systemic therapy for advanced disease were enrolled in the Phase III MONALEESA-2 trial (NCT01958021); 295 patients were aged ≥ 65 years. Patients were randomized to ribociclib (600 mg/day; 3-weeks-on/1-week-off) plus letrozole (2.5 mg/day) or placebo plus letrozole until disease progression, unacceptable toxicity, death, or treatment discontinuation. The primary endpoint was PFS, which was evaluated in elderly (≥ 65 years) and younger (< 65 years) patients. Secondary endpoints included response rates and safety. RESULTS: Ribociclib plus letrozole significantly improved PFS vs placebo plus letrozole in elderly (hazard ratio: 0.608; 95% CI 0.394–0.937) and younger patients (hazard ratio: 0.523; 95% CI 0.378–0.723). Overall response rates were numerically higher in the ribociclib vs placebo arm, regardless of age. Ribociclib plus letrozole was well tolerated in elderly patients, with the safety profile similar to the overall study population. Nausea, vomiting, alopecia, and diarrhea were > 10% more frequent in the ribociclib plus letrozole vs placebo plus letrozole arm in both subgroups; most events were grade 1/2. In elderly patients, grade 1/2 anemia and fatigue were > 10% more frequent in the ribociclib plus letrozole vs placebo plus letrozole arm and discontinuation rates were similar in both arms. CONCLUSIONS: Addition of ribociclib to letrozole is a valid therapeutic option for elderly patients with HR+, HER2− advanced breast cancer in the first-line setting.